Contradictions of the health-care system in India and a strategy for health-care for all - Anant Phadke (Wolters Kluwer Medknow Publications, 2013)
The contradiction between the socialized nature of the modern health-care system (inclusive of both clinical and social medicine) versus the narrow control over it is obvious in private health-care. However, this contradiction is present to some extent, in its own way, even in the public health facilities in India. To formulate a program for health-care for all in India, it is necessary to grasp these contradictions in both private and public health-care and accordingly conceptualize a strategy to overcome, resolve these contradictions.